2012
DOI: 10.4136/ambi-agua.972
|View full text |Cite
|
Sign up to set email alerts
|

Influência de características físico-químicas da água no transporte de metano para a atmosfera na Lagoa Rodrigo de Freitas, RJ

Abstract: Influência de características físico-químicas da água no transporte de metano para a atmosfera na Lagoa Rodrigo deFreitas, RJ (http://dx.doi.org/10.4136/ambi-agua.972) RESUMOO acúmulo e a decomposição de matéria orgânica em corpos d'água pode incrementar o potencial de emissão de gases de efeito estufa à atmosfera. Neste trabalho, de modo prospectivo e exploratório, foi avaliada a relação entre características físico-químicas da água e o transporte de metano para a atmosfera na Lagoa Rodrigo de Freitas, RJ, em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Rodrigo de Freitas Lagoon has a very inefficient water exchange, but it is not like Três Palos Lagoon that did not connect with the sea most of the year. Braz et al (2012), in their study also in Rodrigo de Freitas Lagoon, found an average of 33 mg m -2 d -1 in two collections performed in the summer. These values were lower than those presented in this study.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Rodrigo de Freitas Lagoon has a very inefficient water exchange, but it is not like Três Palos Lagoon that did not connect with the sea most of the year. Braz et al (2012), in their study also in Rodrigo de Freitas Lagoon, found an average of 33 mg m -2 d -1 in two collections performed in the summer. These values were lower than those presented in this study.…”
Section: Discussionmentioning
confidence: 86%
“…These values were lower than those presented in this study. However, Braz et al (2012) have analyzed only five sites in the Lagoon that did not have the highest values for methane emission, such as the General Garzon Region, which may explain this difference. Cotovicz et al (2016) also found positive methane fluxes from the Guanabara Bay, a eutrophic estuary in the city of Rio de Janeiro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A positi ve ORP value was also found when associated with pH (Table 4, row 2, column 3) and OD (Table 4, row 6, column 3), being possible when there is a larger amount of organic solid within the system leading the pH to be more acid, increasing the oxygen consumpti on (BRAZ et al, 2012).…”
Section: Water Quality Of the Human Consumption Supply System In The mentioning
confidence: 88%